2021
DOI: 10.1186/s12879-021-05935-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and healthcare costs of inpatients with tetanus in Korea, 2011–2019

Abstract: Background Tetanus is a rare, vaccine-preventable but extremely serious disease. We investigated the recent trend of the clinical outcomes and medical costs for inpatients with tetanus in South Korea over 10 years. Methods We conducted a retrospective review to determine the clinical factors and medical costs associated with tetanus at two national university hospitals in South Korea between January 2011 and October 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…Postoperatively, the intraoperative cultures grew methicillinsensitive Staphylococcus aureus (MSSA), with no anaerobic growth, so his antibiotics were transitioned to cefazolin. He was noted 2 days later to have improved symptoms, with a total length of stay lasting 15 days, less than that in some previous reports where systemic tetanus involved a median hospital stay of 10 to 39 days 2,5,6 . The patient was discharged with a 4-week course of cefalexin to treat his osteomyelitis, and diazepam for muscle spasms.…”
Section: Case Reportcontrasting
confidence: 53%
See 1 more Smart Citation
“…Postoperatively, the intraoperative cultures grew methicillinsensitive Staphylococcus aureus (MSSA), with no anaerobic growth, so his antibiotics were transitioned to cefazolin. He was noted 2 days later to have improved symptoms, with a total length of stay lasting 15 days, less than that in some previous reports where systemic tetanus involved a median hospital stay of 10 to 39 days 2,5,6 . The patient was discharged with a 4-week course of cefalexin to treat his osteomyelitis, and diazepam for muscle spasms.…”
Section: Case Reportcontrasting
confidence: 53%
“…Differential diagnosis for bacterial infection includes S. aureus, Escherichia coli , Streptococcus pyogenes , Klebsiella pneumonia , and/or anaerobic bacteria such as Peptostreptococcus spp , Prevotella spp , Fusobacterium spp , Bacteroides fragilis group, and Clostridium spp 6,8 . A diagnosis of C. tetani is more likely when systemic symptoms outweigh localized findings, such as a lack of blistering around the wound or imaging that does not demonstrate the feathering pattern of gas in soft tissue, typical of gas forming organisms such as Clostridium perfringens .…”
Section: Discussionmentioning
confidence: 99%
“…Globally, 48,000–80,000 patients die due to tetanus every year, with most of these deaths occurring in low- and middle-income countries [ 9 ]. Additionally, the length of hospitalization is longer in severe cases, and subsequent treatments due to delays cause high medical fees, increasing the financial burden of patients [ 10 ]. Therefore, early identification of severe tetanus patients and administration of high-dose sedatives to alleviate muscle spasms as well as prompt tracheotomy to prevent asphyxiation are vital [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to focus on the first manifestations and departments visited first among patients with tetanus in countries with a low prevalence. Some studies have reported that the most common symptom was trismus, but these studies examined the symptoms on hospital admission [12][13][14]. In the literature in Japanese on the clinical characteristics of tetanus, 6/11 (55%) patients did not present with trismus as an initial symptom, but the investigation did not focus on the visited department before the diagnosis [15].…”
Section: Discussionmentioning
confidence: 99%